New Accountabilities, New Challenges - Wanna, John; A. Lindquist, Evert; Marshall, Penelope (ANU Press, 2015)
This important and challenging volume of essays draws on insights from leading academics and public servants from Australia, New Zealand, the United Kingdom, Canada and elsewhere. It provides an excellent series of critiques of both the systemic accountabilities and the policy processes of government by drawing on meticulously researched, topical and real-world case studies of governance. Its contribution to the understanding of the applied processes of government in this way is exemplary. Topics covered include: restoring trust in government, parliamentary scrutiny of the APS, administrative law and FOI, budgetary reforms, implementation issues, competition policy, indigenous administration, collaboration with the NGO sector, educational reforms and the changes to the Auditor- General's mandate.